Intriguing Sum

Calculus Level 5

Define S S as

S = n = 1 ( 2 n n ) n × 4 n S = \sum_{n=1}^{\infty} \frac{\binom{2n}{n}}{n \times 4^{n}}

What is the value of e S e^{S} ?


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

C o n s i d e r : I ( n ) = 0 π 2 sin 2 n x d x I ( n ) = 2 n 1 2 n I ( n 1 ) , I ( 0 ) = π 2 I ( n ) = ( 2 n 1 ) ( 2 n 3 ) ( 2 n 5 ) . . . . ( 1 ) ( 2 n ) ( 2 n 2 ) ( 2 n 4 ) . . . ( 2 ) × π 2 I ( n ) = ( 2 n n ) × π 2 × 2 2 n ( 2 n n ) n × 4 n = 2 π 0 π 2 sin 2 n x n d x C o n s i d e r : log ( 1 t ) = t + t 2 2 + t 3 3 + t 4 4 + . . . log ( 1 sin 2 t ) = sin 2 t + ( sin 2 t ) 2 2 + ( sin 2 t ) 3 3 + ( sin 2 t ) 4 4 + . . . n = 1 ( 2 n n ) n × 4 n = 2 π 0 π 2 ( sin 2 t + ( sin 2 t ) 2 2 + ( sin 2 t ) 3 3 + ( sin 2 t ) 4 4 + . . . ) d t n = 1 ( 2 n n ) n × 4 n = S = 2 π 0 π 2 log ( 1 sin 2 t ) d t S = 2 π 0 π 2 2 log ( cos t ) d t = log 4 e S = 4 Consider:\quad I(n)=\int _{ 0 }^{ \frac { \pi }{ 2 } }{ \sin ^{ 2n }{ x } } dx\\ \\ \Rightarrow I(n)=\frac { 2n-1 }{ 2n } I(n-1)\quad ,\quad I(0)=\quad \frac { \pi }{ 2 } \\ \\ \Rightarrow I(n)\quad =\frac { (2n-1)(2n-3)(2n-5)....(1) }{ (2n)(2n-2)(2n-4)...(2) } \times \frac { \pi }{ 2 } \\ \\ \Rightarrow I(n)\quad =\left( \begin{matrix} 2n \\ n \end{matrix} \right) \times \frac { \pi }{ 2 } \times { 2 }^{ -2n }\quad \\ \Rightarrow \frac { \left( \begin{matrix} 2n \\ n \end{matrix} \right) }{ { n\times 4 }^{ n } } =\frac { 2 }{ \pi } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ \frac { \sin ^{ 2n }{ x } }{ n } } dx\\ Consider:\quad -\log { (1-t) } =t+\frac { { t }^{ 2 } }{ 2 } +\frac { { t }^{ 3 } }{ 3 } +\frac { { t }^{ 4 } }{ 4 } +...\\ \Rightarrow -\log { (1-\sin ^{ 2 }{ t } ) } =\sin ^{ 2 }{ t } +\frac { { (\sin ^{ 2 }{ t } ) }^{ 2 } }{ 2 } +\frac { { (\sin ^{ 2 }{ t } ) }^{ 3 } }{ 3 } +\frac { { (\sin ^{ 2 }{ t } ) }^{ 4 } }{ 4 } +...\\ \Rightarrow \sum _{ n=1 }^{ \infty }{ \frac { \left( \begin{matrix} 2n \\ n \end{matrix} \right) }{ { n\times 4 }^{ n } } } =\frac { 2 }{ \pi } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ (\sin ^{ 2 }{ t } +\frac { { (\sin ^{ 2 }{ t } ) }^{ 2 } }{ 2 } +\frac { { (\sin ^{ 2 }{ t } ) }^{ 3 } }{ 3 } +\frac { { (\sin ^{ 2 }{ t } ) }^{ 4 } }{ 4 } +... } )dt\\ \Rightarrow \sum _{ n=1 }^{ \infty }{ \frac { \left( \begin{matrix} 2n \\ n \end{matrix} \right) }{ { n\times 4 }^{ n } } } =S=\frac { 2 }{ \pi } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ -\log { (1-\sin ^{ 2 }{ t } ) } } dt\\ \Rightarrow S=\frac { 2 }{ \pi } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ -2\log { (\cos { t } ) } } dt=\log { 4 } \\ \Rightarrow { e }^{ S }=\boxed { 4 }

Log in to reply

i did it the same way

Atul Antony Zachariahs - 6 years, 2 months ago

Nice solution +1, but I did mine using generating functions so it can be more general ^^

Oussama Boussif - 6 years, 2 months ago

Here's another way Let ( 1 + m x ) n { \left( 1+mx \right) }^{ n } = 1 + n = 1 ( 2 n n ) 4 n 1+\sum _{ n=1 }^{ \infty }{ \frac { \left( \begin{matrix} 2n \\ n \end{matrix} \right) }{ { 4 }^{ n } } } x n { x }^{ n }

comparing coefficents of x and x 2 { x }^{ 2 }

mn=1/2 and m 2 {m}^{2} n(n-1)/2=1.3/2.4

solving we get m=-1,n=-1/2,we can easily check if other terms are also as in the first expression

So 1 ( 1 x ) 1 / 2 = 1 + ( 2 1 ) x 4 1 + ( 4 2 ) x 2 4 2 + . . . . . \frac { 1 }{ { (1-x) }^{ 1/2 } } =1+\frac { \left( \begin{matrix} 2 \\ 1 \end{matrix} \right) x }{ { 4 }^{ 1 } } +\frac { \left( \begin{matrix} 4 \\ 2 \end{matrix} \right) { x }^{ 2 } }{ { 4 }^{ 2 } } +.....

Taking 1 to the other side , and dividing by x and then integrating from x=0 to x=1 we get,

0 1 1 x ( 1 x ) 1 / 2 1 x d x = 0 1 ( 2 1 ) 4 1 + ( 4 2 ) x 1 4 2 + . . . . . d x \int _{ 0 }^{ 1 }{ \frac { 1 }{ { x(1-x) }^{ 1/2 } } - } \frac { 1 }{ x }dx =\int _{ 0 }^{ 1 }\frac { \left( \begin{matrix} 2 \\ 1 \end{matrix} \right) }{ { 4 }^{ 1 } } +\frac { \left( \begin{matrix} 4 \\ 2 \end{matrix} \right) { x }^{ 1 } }{ { 4 }^{ 2 } } +..... dx

On performing this integration ,on we get,

l o g ( 4 ) = ( 2 1 ) 4 1 . 1 1 + ( 4 2 ) 4 2 . 1 2 + . . . . . log(4)=\frac { \left( \begin{matrix} 2 \\ 1 \end{matrix} \right) }{ { 4 }^{ 1 } } .\frac { 1 }{ 1 } +\frac { \left( \begin{matrix} 4 \\ 2 \end{matrix} \right) }{ { 4 }^{ 2 } } .\frac { 1 }{ 2 } +..... which is equal to s

Hence e^s=4

Arey yaar! This is better. Shame that I don't know taylor series for negative or rational exponents :/

Raghav Vaidyanathan - 6 years, 2 months ago

Log in to reply

Check out "Newton's Generalized Binomial theorem" here

Kartik Sharma - 6 years, 2 months ago
Joshua Yip
Apr 11, 2015

In the series, ( 2 n n ) \left( \begin{matrix} 2n \\ n \end{matrix} \right) is the central binomial coefficient. However there are no exact formula of ( 2 n n ) \left( \begin{matrix} 2n \\ n \end{matrix} \right) , but we can use approximations. One good approximation is by using more terms in the Stirling series. We get

( 2 n n ) = 4 n π n ( 1 1 8 n + 1 128 n 2 + 5 1024 n 3 21 32768 n 4 + O ( n 5 ) ) \left( \begin{matrix} 2n \\ n \end{matrix} \right) =\frac { 4^{ n } }{ \sqrt { \pi n } } \left( 1-\frac { 1 }{ 8n } +\frac { 1 }{ 128n^{ 2 } } +\frac { 5 }{ 1024n^{ 3 } } -\frac { 21 }{ 32768n^{ 4 } } +O(n^{ -5 }) \right)

where O ( n 5 ) O(n^{ -5 }) is the Big O notation. Then we have

s n = 1 4 n π n ( 1 1 8 n + 1 128 n 2 + 5 1024 n 3 21 32768 n 4 ) n × 4 n s\sim\sum _{ n=1 }^{ \infty }{ \frac { \frac { 4^{ n } }{ \sqrt { \pi n } } \left( 1-\frac { 1 }{ 8n } +\frac { 1 }{ 128n^{ 2 } } +\frac { 5 }{ 1024n^{ 3 } } -\frac { 21 }{ 32768n^{ 4 } } \right) }{ n\times 4^{ n } } }

= n = 1 1 1 8 n + 1 128 n 2 + 5 1024 n 3 21 32768 n 4 n π n =\sum _{ n=1 }^{ \infty }{ \frac { 1-\frac { 1 }{ 8n } +\frac { 1 }{ 128n^{ 2 } } +\frac { 5 }{ 1024n^{ 3 } } -\frac { 21 }{ 32768n^{ 4 } } }{ n\sqrt { \pi n } } }

= 1 π n = 1 1 1 8 n + 1 128 n 2 + 5 1024 n 3 21 32768 n 4 n n =\frac { 1 }{ \sqrt { \pi } } \sum _{ n=1 }^{ \infty }{ \frac { 1-\frac { 1 }{ 8n } +\frac { 1 }{ 128n^{ 2 } } +\frac { 5 }{ 1024n^{ 3 } } -\frac { 21 }{ 32768n^{ 4 } } }{ n\sqrt { n } } }

= 1 π ( n = 1 1 n n 1 8 n = 1 1 n 2 n + 1 128 n = 1 1 n 3 n + 5 1024 n = 1 1 n 4 n 21 32768 n = 1 1 n 5 n ) =\frac { 1 }{ \sqrt { \pi } } \left( \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n\sqrt { n } } } -\frac { 1 }{ 8 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ 2 }\sqrt { n } } } +\frac { 1 }{ 128 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ 3 }\sqrt { n } } } +\frac { 5 }{ 1024 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ 4 }\sqrt { n } } } -\frac { 21 }{ 32768 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ 5 }\sqrt { n } } } \right)

= 1 π ( n = 1 1 n 3 2 1 8 n = 1 1 n 5 2 + 1 128 n = 1 1 n 7 2 + 5 1024 n = 1 1 n 9 2 21 32768 n = 1 1 n 11 2 ) =\frac { 1 }{ \sqrt { \pi } } \left( \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ \frac { 3 }{ 2 } } } } -\frac { 1 }{ 8 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ \frac { 5 }{ 2 } } } } +\frac { 1 }{ 128 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ \frac { 7 }{ 2 } } } } +\frac { 5 }{ 1024 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ \frac { 9 }{ 2 } } } } -\frac { 21 }{ 32768 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ \frac { 11 }{ 2 } } } } \right)

Applying Riemann zeta function, we get

= 1 π ( ζ ( 3 2 ) 1 8 ζ ( 5 2 ) + 1 128 ζ ( 7 2 ) + 5 1024 ζ ( 9 2 ) 21 32768 ζ ( 11 2 ) ) =\frac { 1 }{ \sqrt { \pi } } \left( \zeta \left( \frac { 3 }{ 2 } \right) -\frac { 1 }{ 8 } \zeta \left( \frac { 5 }{ 2 } \right) +\frac { 1 }{ 128 } \zeta \left( \frac { 7 }{ 2 } \right) +\frac { 5 }{ 1024 } \zeta \left( \frac { 9 }{ 2 } \right) -\frac { 21 }{ 32768 } \zeta \left( \frac { 11 }{ 2 } \right) \right)

After evaluation, we get approximately s = 1.3867695148 s=1.3867695148 .

e s = 4.001901 { e }^{ s }=4.001901 which is approximately 4 \boxed{4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...